Peculiarities of the Russian and German Energy Policies in the Field of Alternative Energy Development - Shuvalova, Olga Vladimirovna; Chernyaev, Maxim Vasilyevich; Rodionova, Irina Aleksandrovna; Korenevskaya, Anna Vadimovna (International Journal of Energy Economics and Policy, 2018)
This article is purported to analyze the experience of energy policy implemented by governments of Germany and Russia in the field of alternative energy, and assess a possibility of applying an accumulated experience of foreign countries in today’s Russian environment. The profitability of energy production based on usage of alternative sources is still substantially lower compared to energy production based on fossil fuels combustion process. Governmental measures aimed at developing alternative energy include the following ones: formation of a new pricing policy, shifting towards alternative energy sources, use of insurance schemes, establishment of a minimum level of prices for energy produced from utilization of alternative energy sources, etc. A lot of countries have accomplished a long process in the field alternative energy technology introduction. Meanwhile Russia, in spite of its considerable experience of alternative energy development in the second half of the 20th century during the Soviet period, is not yet in line with the latest world progress in this field. Keywords: alternative energy sources, energy resources, German and Russian Energy Policy JEL Classifications: Q40, Q42